A systematic approach to capacity strengthening of laboratory systems for control of neglected tropical diseases in Ghana, Kenya, Malawi and Sri Lanka. - Janet Njelesani; Russell Dacombe; Tanith Palmer; Helen Smith; Benjamin Koudou; Moses Bockarie; Imelda Bates (PLoS Neglected Tropical Diseases)
Background The lack of capacity in laboratory systems is a major barrier to achieving the aims of the London Declaration (2012) on neglected tropical diseases (NTDs). To counter this, capacity strengthening initiatives have been carried out in NTD laboratories worldwide. Many of these initiatives focus on individuals' skills or institutional processes and structures ignoring the crucial interactions between the laboratory and the wider national and international context. Furthermore, rigorous methods to assess these initiatives once they have been implemented are scarce. To address these gaps we developed a set of assessment and monitoring tools that can be used to determine the capacities required and achieved by laboratory systems at the individual, organizational, and national/international levels to support the control of NTDs. Methodology and principal findings We developed a set of qualitative and quantitative assessment and monitoring tools based on published evidence on optimal laboratory capacity. We implemented the tools with laboratory managers in Ghana, Malawi, Kenya, and Sri Lanka. Using the tools enabled us to identify strengths and gaps in the laboratory systems from the following perspectives: laboratory quality benchmarked against ISO 15189 standards, the potential for the laboratories to provide support to national and regional NTD control programmes, and the laboratory's position within relevant national and international networks and collaborations. Conclusion We have developed a set of mixed methods assessment and monitoring tools based on evidence derived from the components needed to strengthen the capacity of laboratory systems to control NTDs. Our tools help to systematically assess and monitor individual, organizational, and wider system level capacity of laboratory systems for NTD control and can be applied in different country contexts.